Associations Between Strong Earthquakes and Local Rainfall in China - Zhao, Dajun; Chen, Lianshou; Yu, Yubin (Frontiers in Earth Science, 2021)
Strong earthquakes are a major cause of natural disasters and may also be related to heavy rainfall events. Both phenomena have received considerable attention in seismology and meteorology, two relatively independent disciplines, but we do not yet know whether there is a connection between them. We investigated the characteristics of daily rainfall over seismic areas in China. Our statistical analyses showed that there is a strong correlation between strong earthquakes (Ms ≥ 6.0) and rainfall over the seismic area, with 74.9% of earthquakes in China accompanied by seismic epicenter rainfall and 86.6% by seismic area rainfall. The statistics also showed that the daily precipitation over the seismic area, including the epicenter, was mainly light rain, with only a few instances of torrential or storm rain, with 80% of the rainfall events lasting two or more days. The maximum cumulative precipitation corresponded well with the strong earthquakes occurring over steep terrain, such as the central Taiwan mountains and the eastern Tibetan Plateau. The earthquake area rainfall had a higher frequency than the 30-year climatological average and was dominated by earthquake events in the wet season. The WRF-ARW numerical simulation of seismic local rainfall during the devastating Ms 8.0 Wenchuan earthquake in May 2008 showed that the geothermal heat from the earthquake strengthened the local convergence of moisture and vertical motion near the epicenter and the upward transport of the sensible heat flux, which favored seismic rainfall. The results of this study show that rainfall in the seismic area is closely related to strong earthquakes and can be triggered and enhanced by geothermal heat.